2021
DOI: 10.3389/pore.2021.581395
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Osteopontin Expression Inhibits Proliferation, Invasion and Induce Altered Protein Expression in Melanoma Cells

Abstract: Osteopontin (OPN) is a multifunctional phosphoprotein that is expressed in different types of cancers, including melanoma. OPN overexpression is associated with tumor progression and metastasis formation; however, the role of OPN in cell invasion and metastasis formation is not completely understood. In this study we aimed to define OPN expression in melanoma tissues and cell lines and investigate the effect of OPN expression on cell proliferation and invasion after inhibiting OPN expression with small interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Osteopontin (OPN), a multifunctional protein, has been widely studied as a promising biomarker in various types of tumors for monitoring tumor progression, invasion, metastasis formation and drug resistance (13,25). The association between the aberrant expression of osteopontin and melanoma invasion, metastasis formation, and radio/drug resistance has been recently described (1,3,(25)(26)(27). The biological functions of tumor-associated gene products are extensively regulated via pre-and posttranscriptional modifications, resulting in alternative splicing of OPN.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin (OPN), a multifunctional protein, has been widely studied as a promising biomarker in various types of tumors for monitoring tumor progression, invasion, metastasis formation and drug resistance (13,25). The association between the aberrant expression of osteopontin and melanoma invasion, metastasis formation, and radio/drug resistance has been recently described (1,3,(25)(26)(27). The biological functions of tumor-associated gene products are extensively regulated via pre-and posttranscriptional modifications, resulting in alternative splicing of OPN.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially found in bone, but later research revealed that it is expressed in several tissues [2,3]. OPN mediates a multitude of biological processes and plays significant roles in biomineralization, and a number of physiological processes involved in cellular homeostasis, as well as in pathologies such as chronic inflammation and tumor biology [4][5][6]. OPN was also known as early T-lymphocyte activation 1 protein, and bone sialoprotein 1 [7] and was reported to activate immune cells, including T-cells, B-cells, macrophages, natural killer and Kupffer cells [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…SPP1 mediates chemotherapy resistance in prostate cancer [ 41 ]. In addition, some scholars have demonstrated that inhibition of SPP1 expression can inhibit the progression of melanoma [ 42 ]. These evidences suggest that SPP1 plays a role in promoting the progression of various cancers.…”
Section: Discussionmentioning
confidence: 99%